Long-term Pooled Safety Analysis of Palbociclib in Combination With Endocrine Therapy for HR+/HER2- Advanced Breast Cancer. (18th July 2018) - Diéras, Véronique; Rugo, Hope S; Schnell, Patrick; Gelmon, Karen; Cristofanilli, Massimo; Loi, Sherene; Colleoni, Marco; Lu, Dongrui R; Mori, Ave; Gauthier, Eric; Huang Bartlett, Cynthia; Slamon, Dennis J; et al.
Abstract: Background: Palbociclib administered with endocrine therapy was tolerable when the overall incidence of toxicities was assessed separately for three PALOMA studies. This study analyzed pooled, longer-term PALOMA safety data longitudinally. Methods: Data were pooled from three randomized phase II and III studies (ClinicalTrials.gov: NCT00721409, NCT01740427, NCT01942135) of hormone receptor–positive/human epidermal growth factor receptor 2‒negative advanced breast cancer patients. Front-line patients were randomly assigned to receive letrozole with/without palbociclib (PALOMA-1) or letrozole plus palbociclib/placebo (PALOMA-2). In PALOMA-3, patients with prior endocrine resistance received fulvestrant plus palbociclib/placebo. The cumulative event rates of adverse events (AEs), reporting up to 50 months of treatment, were assessed over time. Results: Patients who received endocrine therapy (n = 1343) were included in this pooled analysis (872 were also treated with palbociclib, and 471 were not). The most common AEs with palbociclib plus endocrine therapy were neutropenia and infections (any grade, 80.6% and 54.7%, respectively), which were higher than in the endocrine monotherapy arm (any grade, 5.3% and 36.9%). The most common hematologic AEs (≥15.0% in the palbociclib arm) were more likely to be reported in the initial months of the study, after which time the cumulative event rate did not substantially increase. With palbociclib plus endocrine therapy, any grade AEs leading to permanent discontinuation over three years occurred in only 8.3% of patients. Conclusions: Based on these long-term safety analyses, there is no evidence of specific cumulative or delayed toxicities with palbociclib plus endocrine therapy, supporting the ongoing investigation of palbociclib plus endocrine therapy in early breast cancer (NCT02513394).